PENGARUH MODEL PROBLEM BASED INSTRUCTION TERHADAP SELF EFFICACY DAN HASIL BELAJAR SISWA - Arfiyana Destaria Tarmizi; Arwin Surbakti; Rini Rita T Marpaung (Universitas Lampung, 2015)
The purpose of this research was to know the influence of PBI model to self efficacy and students learning outcomes on the influence of population density to environment subject matter. The design of this research was control group pretest-posttest. The samples of this research were the students at VIIA and VIIB SMPN 2 Seputih Mataram which were chosen by purposive sampling. The learning outcomes were analyzed statistically by using one way anova. The qualitative data were the increasing of self efficacy which were obtained from questionaire and analyzed descriptively. The result showed that the average of self efficacy in experiment class (76) was higher than control class (67,8) and students learning outcomes increased significantly with the average in experiment class (62,2) and control class (54). Based on this research, it can be concluded that the PBI model gave influence to self efficacy and students learning outcomes.Penelitian ini bertujuan untuk mengetahui pengaruh model PBI terhadap Self efficacy dan hasil belajar siswa pada materi pokok pengaruh kepadatan populasi manusia terhadap lingkungan. Desain penelitian ini control group pretest postest. Sampel adalah siswa kelas VIIA dan VIIB SMPN 2 Seputih Mataram dengan teknik purposive sampling. Data hasil belajar dianalisis dengan Anova satu jalur. Data kualitatif berupa peningkatan self efficacy yang diperoleh melalui angket yang dianalisa secara deskriptif. Hasil penelitian menunjukkan rata-rata self efficacy kelas eksperimen (76) lebih tinggi dari kelas kontrol (67,8) dan hasil belajar siswa meningkat signifikan dengan rata-rata nilai kelas eksperimen (62,2) dan kelas kontrol (54). Berdasarkan hasil penelitian dapat disimpulkan bahwa model pembelajaran PBI berpengaruh terhadap self efficacy dan hasil belajar siswa.Kata kunci: hasil belajar, PBI, self efficacy